2013
DOI: 10.1007/s11743-013-1507-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solubility Efficiency of Polycyclic Aromatic Hydrocarbons in Single Surfactant Systems

Abstract: Water solubility enhancements of two polycyclic aromatic hydrocarbons i.e., naphthalene (Naph) and anthracene (Anth) in single surfactants system have been measured by UV–VIS‐Spectrophotometer. The relationships between solubilizing capacity and their solubilization efficiency towards polycyclic aromatic hydrocarbons (PAH) have been quantified and discussed in terms of the molar solubilization ratio (MSR), the micelle‐water partition coefficient (Km) and standard free energy of solubilization (ΔG°s). The micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
(71 reference statements)
2
14
0
1
Order By: Relevance
“…The CMC values obtained from the conductivity method are in good agreement with the surface tension and fluorescence methods. The experimental CMC values are in close agreement with published literature data [24,28,[37][38][39][40]54]. It is observed that an increase in the amount of EG and DEG increases the degree of ionization for all the studied surfactants.…”
Section: Cetyldimethylethanolammonium Bromide (Cdmeab)supporting
confidence: 90%
“…The CMC values obtained from the conductivity method are in good agreement with the surface tension and fluorescence methods. The experimental CMC values are in close agreement with published literature data [24,28,[37][38][39][40]54]. It is observed that an increase in the amount of EG and DEG increases the degree of ionization for all the studied surfactants.…”
Section: Cetyldimethylethanolammonium Bromide (Cdmeab)supporting
confidence: 90%
“…The lower the CMC value, the higher the solubilizing power. Surfactants with lower CMC values possess greater solubilizing efficiency [27]. We have already reported the CMC of investigated gemini and monomeric cationic surfactants in aqueous solution in Table 2 [27,44,45].…”
Section: Micellar Solubilizationmentioning
confidence: 99%
“…The concentration of hydrophobic compounds increases with the addition of surfactants in the water phase by solubilization or emulsification [24,25]. In recent years, a considerable amount of research has been conducted on the SER of PAHs [26][27][28][29][30][31]. Most of the work on surfactant solubilization of hydrophobic organic compounds (HOCs) has focused on the conventional monomeric anionic, cationic and nonionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezt a tenzidet ugyanis a 60-as évek-től kezdve használták a talajok, illetve üledékek fajlagos felületének gyors meghatá-rozására, így különösen sokat vizsgálták a CPB adszorpciójára ható talaj-és talajás-ványtani tulajdonságokat ARINGHIERI & SEQUI, 1978;MAYER & ROSSI, 1982). A két vegyületet az adszorpcióban főszerepet játszó azonos kation miatt gyakran együtt jellemzik, mint vegyület-csoportot (cetilpiridinium-halogenidek -CPH) (LAKRA et al, 2013), így a továbbiakban mi is összevontan mutatjuk be a két tenzid talajokon történő adszorpciójának törvénysze-rűségeit tárgyaló kutatási eredményeket.…”
Section: B Evezetésunclassified